Socio-Economic Aspects and the Commercialization of Rural Mising People: Special Emphasis Related To Mising Community of Bishwanath District In Assam, India - et. al., Indeswar Pegu, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The direction of commercialization is very relevant in building the economic foundation of a society. With the development of human civilization, the commercialization and market system has affected the rural areas. The abolition of the old-fashioned barter system has given rise to a new way of thinking and meeting the needs of the human mind. The issue of commercialization is more important than the economic aspects of a society and issues of livelihood as well as demand. If there is no need for human beings and there is no need to meet the need, then the idea of commercialization is also absurd. This research paper analyzes how the meetings in rural areas of Assam have commercialized the products for socio-economic upliftment and its impact on the four Mising villages of Bishwanath district as the main resource.